Adjudicating outcomes in stroke trials - Godolphin, Peter J. (2019)
Central adjudication in randomised trials refers to the evaluation of outcome data by independent experts who are typically part of an event or outcome adjudication committee. Alternatively, local site investigators can assess outcomes, but these evaluations are often discarded in favour of the centrally adjudicated outcome. Central adjudication is thought to improve the precision of treatment effect estimates by reducing random error (non-differential misclassification), and in open-label studies adjudication has the potential to limit systematic error (differential misclassification) as adjudicators can always be blinded to treatment allocation.